Magnitude and Its Associated Factors of Urinary Tract Infection among Adult Patients Attending Tigray Region Hospitals, Northern Ethiopia, 2019 - Abrha Hailay; Kidane Zereabruk; Guesh Mebrahtom; Woldu Aberhe; Degena Bahrey (International Journal of Microbiology)
Background. Urinary tract infection is a major public health problem in terms of morbidity and mortality worldwide. It ranks as the number one infection which leads to an antibiotic prescription after a physician’s visit. However, there are limited studies done on UTI in Ethiopia. Hence, this study was aimed to assess the magnitude of urinary tract infection and its associated factors among adult patients attending hospitals of the Tigray region, Ethiopia. Methods and Material. A hospital-based cross-sectional study was conducted from April to May 2019. Systematic random sampling technique was used to select 472 participants from five randomly selected hospitals in Tigray region. A pretested structured questionnaire through face-to-face interview and patient chart review checklist was used to collect data. Data were analyzed by SPSS version 21. A binary logistic regression model was used to test the association between dependent and independent variables. Result. The magnitude of urinary tract infection was 86 (18.2%) (95% CI: 14.6%–21.6%). After adjustment of the independent variables, the significant factors associated with urinary tract infection were being female (AOR = 3.50; 95% CI: 1.88–6.51), urine passing frequency < five times in a day (AOR = 2.32; 95% CI: 1.08–4.96), having diabetes mellitus (AOR = 4.03; 95% CI: 1.69–9.63), history of urinary tract infection (AOR = 4.40; 95% CI: 2.31–8.39), <7 glasses of water intake per day (AOR = 2.16; 95% CI: 1.02–4.58), and history of urinary obstructive diseases (AOR = 2.67; 95% CI: 1.03–6.90). Conclusion and Recommendation. The magnitude of urinary tract infection was considerably high. The factors associated with urinary tract infection were sex, less urine passing frequency, diabetes mellitus, low water intake, history of urinary tract infection, and urinary obstructive diseases. Therefore, patients having DM, previous history of UTI, and urinary obstructive diseases should be routinely screened for urinary tract infection and provided with education on voiding urine at least five times a day and on increasing daily water intake.